Liability for Damage as a Remedy for Infringement of Data Protection rights – Implications for legislation and practice in North Macedonia - Zdraveva, Neda (SEE  EU Cluster of Excellence in European and International Law, 2021)
The Charter of Fundamental Rights of the European Union1 Article 8(1) and the Treaty on the Functioning of the European Union2 Article 16(1) provide that everyone has the right to the protection of personal data concerning them. The General Data Protection Regulation3 operationalizes this fundamental right, laying down rules relating to the protection of natural persons when it comes to the processing of personal data and rules relating to the free movement of personal data. The GDPR provides a general right for an effective judicial remedy and a specific right to compensation for damage suffered as a result of an infringement of the Regulation. GDPR changes or adds to the landscape of the national tort law systems. This paper provides an overview and analysis of the key features of the non-contractual liability for a data breach as provided by the GDPR. It also identifies several issues that may lead to differences in the application of the GDPR in the Member States. The key issues at stake are first whether and how the liability for damage, as a remedy provided in GDPR, influences the legislation in North Macedonia, a candidate country, and second how it may influence the implementation of this remedy in the practice. The author concludes that the mechanisms existing in the national legislation provide for an effective and efficient remedy of the data protection rights.
Keywords: GDPR, liability, damage, data protection, Macedonian Law